Precision Agriculture '25 - John V. Stafford (Brill | Wageningen Academic, 2025)
These edited proceedings contain 181 peer reviewed papers presented at the 15th European Conference on Precision Agriculture, organized by Universitat Politècnica de Catalunya, June 29 – 3 July 2025, in Barcelona, Spain. The papers reflect the wide range of disciplines that impinge on precision agriculture - technology, crop science, soil science, agronomy, information technology, decision support, remote sensing, data analysis and others. Precision agriculture is a reality in agriculture and is playing a key role as the industry comes to terms with the environment, market forces, quality requirements, traceability, vehicle guidance and crop management. Sensors now in use in agriculture are generating'Big Data'leading to the use of machine learning and Al - an increasing challenge for agriculture. Research continues to be necessary and needs to be reported and disseminated to a wide audience. The broad range of research topics reported will be a valuable resource for researchers, advisors, teachers and professionals in agriculture long after the conference has finished.